2018
DOI: 10.1021/acschemneuro.8b00355
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of PQQ Enhances Blood-Brain Barrier Permeability and Inhibitory Activity against Amyloidogenic Protein Fibril Formation

Abstract: Several neurodegenerative diseases have a common pathophysiology where selective damage to neurons results from the accumulation of amyloid oligomer proteins formed via fibrilization. Considering that the formation of amyloid oligomers leads to cytotoxicity, the development of chemical compounds that are able to effectively cross the blood-brain barrier (BBB) and inhibit this conversion to oligomers and/or fibrils is essential for neurodegenerative disease therapy. We previously reported that pyrroloquinoline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Therefore, we needed a higher concentration of Aβ fibrils than the molar concentration determined and used in previously published papers (for example, 15 µM [ 11 ] and 22 µM [ 14 ]) to examine its cytotoxicity after disaggregation. The cytotoxicity of the Aβ samples was analyzed using the MTS assay (Promega, Madison, WI, USA), as previously described [ 30 ]. Briefly, the 90 µM Aβ solutions were preincubated in the absence or presence of the disaggregation reagents, and their corresponding solvent controls without Aβ were added to human neuroblastoma SH-SY5Y cells after a 10-fold dilution in a cell culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we needed a higher concentration of Aβ fibrils than the molar concentration determined and used in previously published papers (for example, 15 µM [ 11 ] and 22 µM [ 14 ]) to examine its cytotoxicity after disaggregation. The cytotoxicity of the Aβ samples was analyzed using the MTS assay (Promega, Madison, WI, USA), as previously described [ 30 ]. Briefly, the 90 µM Aβ solutions were preincubated in the absence or presence of the disaggregation reagents, and their corresponding solvent controls without Aβ were added to human neuroblastoma SH-SY5Y cells after a 10-fold dilution in a cell culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…A common feature of the amyloidogenic proteins is that they undergo conformational change from monomeric native to highly ordered β-sheet-rich amyloid fibrils. , Oligomeric aggregates generated during the amyloid fibril formation are thought to be associated with the neurotoxicity and thus the development of neurodegenerative diseases. There are, therefore, many reports on compounds and proteins, which inhibit and/or disassemble the amyloid fibrils. Representative natural compounds are (−)-epigallocatechine-3-gallate (EGCG), which is a type of catechin, curcumin, and pyrroloquinoline quinone (PQQ). , It is also reported that proteins such as molecular chaperones and cyclophilins suppress the amyloid fibril formation. Thus, research studies for finding new compounds and molecules for inhibition and disassembly against amyloid fibrils and clarification of their mechanisms remain a central issue.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the mitochondrion is the rational target so as to ameliorate the damage induced by over exercise. 13,14 Some bioactive substances, such as curcumin, genistein and resveratrol, can promote mitochondrial biogenesis and respiration. [15][16][17] However, curcumin, flavonoids and resveratrol are insoluble in water, which affects their absorption.…”
Section: Introductionmentioning
confidence: 99%
“…which compromise mitochondrial function. Therefore, the mitochondrion is the rational target so as to ameliorate the damage induced by over exercise 13,14 . Some bioactive substances, such as curcumin, genistein and resveratrol, can promote mitochondrial biogenesis and respiration 15‐17 .…”
Section: Introductionmentioning
confidence: 99%